PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT DAN SISTEM PENGHARGAAN TERHADAP PENINGKATAN PRODUKTIVITAS - Yuwono, Rendy; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this study was to examine the effect of total quality management and reward systems of employeeproductivity. The population in this study were employees of PT Darlin Audiya totaling 35 employees, thesampling technique using probability sampling. Data used in the study are primary data questionnaire. Whilethe analytical technique used is multiple regression analysis. Based on the results of the feasibility test modelsknown that variable total quality management and reward systems have a significant effect on employeeproductivity. Based on the next test with menngunakan t test showed that the independent variables havesignificant influence and positive impact on the companys employees, this indicates that the better total qualitymanagement (TQM) and the reward system in the company, it can improve employee productivity, whichmeans the better implementation total quality management and reward systems that can improve employeeproductivity in meeting and serving the needs of consumers. The results of this study would be useful for themanagement company, to further improve the application of the concept of total quality management andreward systems to employees because it can improve employee productivityKeywords: Total quality management, systems, employee productivity award.